Effect of whole-body vibration training on transcutaneous oxygen levels of the foot in patients with type 2 diabetes: A randomized controlled trial. (June 2022) - Rodríguez-Reyes, Gerardo; García-Ulloa, Ana Cristina; Hernández-Jiménez, Sergio; Alessi-Montero, Aldo; Núñez Carrera, Lidia; Rojas-Torres, Francis; Infanzón-Talango, Héctor; Clark, Patricia; Miranda-Duarte, Antonio; Gómez-Díaz, Rita A.
Abstract: Whole body vibration (WBV) has been suggested as improving skin and blood flow. This study aimed to determine the effect of exposure to WBV on levels of partial transcutaneous oxygen pressure (TcPO2) in the foot of patients with type 2 diabetes (T2D) within the metabolic control goals. A block randomized, open, two-arm, parallel and controlled clinical trial was conducted. Participants recruited from the Center of Comprehensive Care for the Patient with Diabetes were assessed at the National Institute of Rehabilitation, Mexico City. Control group underwent multidisciplinary care for T2D; experimental group, in addition to the comprehensive diabetes care, was exposed to WBV through an exercise program, attending three times a week for a period of 3 months. TcPO2 was measured in the feet of the participants at baseline and after 12 weeks. A sample of 50 volunteers with recently-diagnosed T2D and similar baseline characteristics (demographic, cardiovascular risk, presence of diabetic polyneuropathy, and indicators of glycemic control and TcPO2) was recruited. The experimental group (n = 27) showed a mean value of 47.7 ± 6.1 mmHg in TcPO2, significantly higher (p = 0.028) than the 44.3 ± 7.5 mmHg of control group (n = 23), at the end of intervention. In conclusion, exposure to WBV promoted an increase and a significant 3 mmHg difference in the foot TcPO2 levels between those subjects with T2D that underwent the 12-week exercise program and those not exposed to the treatment.